Estimating the Time Since Deposition of Saliva Stains With a Targeted Bacterial DNA Approach: A Proof-of-Principle Study - Díez López, Celia; Kayser, Manfred; Vidaki, Athina (Frontiers in Microbiology, 2021)
Information on the time when a human biological stain was deposited at a crime scene can be valuable in forensic investigations. It can help link a DNA-identified stain donor with a crime or provide with post-mortem interval estimation in cases with human cadavers. Available methods for estimating stain deposition time so far have limitations of different types and magnitudes. In this proof-of-principle study we investigated the use of microbial DNA for this purpose in human saliva stains. First, we identified the most abundant and frequent bacterial species in saliva using publicly available 16S rRNA gene next generation sequencing (NGS) data from 1,848 samples. Next, we assessed time-dependent changes in 15 identified species using de-novo 16S rRNA gene NGS in saliva stains of two individuals exposed to indoor conditions up to one year. We selected four bacterial species i.e., Fusobacterium periodonticum, Haemophilus parainfluenzae, Veillonella dispar, and Veillonella parvula showing statistically significant time-dependent changes and developed a 4-plex qPCR assay for their targeted analysis. Then, we analysed saliva stains of 15 individuals exposed to indoor conditions up to one month. We observed that bacterial counts generally increased with time, which explained 54.9% of the variation (p = <2.2E-16). Time since deposition explained ≥86.5% and ≥88.9% of the variation in each individual and species, respectively (p = <2.2E-16). Finally, based on sample duplicates we built and tested multiple linear regression models for predicting the time since deposition at an individual level, resulting in an average mean absolute error (MAE) of 5 days (ranging 2.9-7.8 days). Overall, the deposition time of 181 (81.5%) stains was correctly predicted within one week. Prediction models were also assessed in stains exposed to the same conditions seven months later, resulting in an average MAE of 8.9 days (ranging 3.9-16.9 days). Our proof-of-principle study suggests the potential of DNA profiling of human commensal bacteria for estimating time since deposition of saliva stains in the forensic scenario, which may be expanded to other forensically relevant tissues. Before our novel approach is considered for practical applications, forensic developmental validation and implementation criteria need to be met via future more dedicated studies.